2011
DOI: 10.5897/sre10.1171
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors for software projects: A comparative study

Abstract: Although there have been studies completed on the critical success factors of software projects, these studies all have been specific to one particular country. There has been no comprehensive study reporting on different project sizes in various domains and in multiple countries. We present our extensive literature survey of critical success factors that impact software projects. Forty-three articles from the years 1990 to 2010 were found to be significant contributions that could be analysed in order to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(26 citation statements)
references
References 70 publications
(83 reference statements)
0
14
0
Order By: Relevance
“…Although a large number of studies categorize CSFs into key areas, suggesting alternative frameworks (e.g. [10], [12], [48], [66]), there is no general categorization of CFS for software projects [67]. To illustrate, many authors have categorized CSFs for either agile or traditional software projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although a large number of studies categorize CSFs into key areas, suggesting alternative frameworks (e.g. [10], [12], [48], [66]), there is no general categorization of CFS for software projects [67]. To illustrate, many authors have categorized CSFs for either agile or traditional software projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some authors (Gupta et al, 2014;Ziemba and Oblak, 2013;Nasir and Sahibuddin, 2011;Huang, 2010) classified CSFs into 3 main groups: human (people-related), organisational (process-and company-related), and technical (software technology-and IT system-related) factor groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hoegl and Gemuenden (2001) and Lindsjørn et al (2016) found a strong correlation between teamwork quality (which includes communication) and the success of software development teams. Nasir and Sahibuddin (2011) conducted a comparative study and found that communication is one of the critical success factors for software projects. The results of Destefanis et al (2016) showed that the level of politeness in the communication process among developers does have an effect on the time required to fix issues in software projects.…”
Section: Introductionmentioning
confidence: 99%